Determining the cadastral-tax areas for the real estate premises based on the model of qualitative and quantitative - Jasińska, Elżbieta; Preweda, Edward (International Conference “Environmental Engineering”, 2017)
The approach to the cadastral value of the property is an indicator of the development of the real estate market, and therefore there are still divisions between countries preferring addictive this value from the surface and from values. The article comments on regulatory presented in selected European Union countries and presents original solution for the determination and correction of the cadastral value of the property, which is the basis to determine the property tax. About the tax character of this value, the fact that the introduction of social concern. Based on Poland, more than twenty years there has been discussion on this subject, but without regulation, there is only a discuss about the concepts of the system. The first attempts spatial analysis in order to determine the cadastral ax areas have not yielded sufficient results, which is why the authors decided to present original solution resulting from the combination of statistical methods inclusive quantitative traits (facet surface) and qualitative characteristics (standard flat) with the characteristics of spatial (location, neighbourhood), in to determine the cadastral value of the property to eventually create the zones in cadastral- tax-zones. As an example, the property from the city Bochnia were used. The paper sought optimal zoning, to minimize variations and create homogeneous collections, which are enclosed areas, so that the weightings were small. To do this, the property housing was selected, as constituting the highest percentage of items on the market.